International Migration and Aspirations among Young People: Who Desires to Migrate? - Sri Purwatiningsih (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2021)
The dispatch of migrant workers from Indonesia is still quite high. Efforts to improve socio- economic status are still motivated by high rates of migration. Children left by migrant parents experience a greater emotional burden due to parenting issues. This study attempts to examine the aspirations of children and adolescents left by migrant parents based on data from the Child Health and Migrant Parents in South East Asia (CHAMPSEA) study. Analytical descriptive was used to describe children’s aspirations towards migrations on migrant and non-migrant households. This study found that children gave a bad perception when mothers had to migrate. Emotional closeness between children and mothers makes the children feel sad when being left by parents. However, once the children’s desire to migrate, especially in the ‘young adult’ group of children is precisely high. Having seen by sex, boys have a higher desire to migrate than women.